Estimation of Chip Crushing Rate - E. M. Dechko (Наука и техника)
In order to analyze chip crushing rate it is proposed to use a sieve analysis and methods of mathematical statistics which are applied in powder metallurgy, peat and coal industries and other branches. Estimation in fluctuation of chip size, stability of its crushing under various cutting conditions, materials and changes of machining conditions have been investigated on the basis of chip fractional composition. Distribution curves and histograms show dominant size of chips. The sieve analysis of chip crushing rate has been applied in deep drilling of steel and grey cast iron.